An Assessment of the Karoon River’s Water Quality Using the Fuzzy Inference Model - M. V; M. N; V. A; A. M.A (مهندسی منابع آب, 2013)
In recent years, the fuzzy-logic-based methods have been developed to consider the intrinsic uncertainty in environmental problems. Noting that the inappropriate classifications that traditional methods apply to develop an index, we intend to develop a better index that measures the river water quality based on the fuzzy logic. Using this approach enabled us to benefit from experts' knowledge in designing the model and mitigating the shortages of previous methods. In the present study, a methodology based on the Fuzzy Inference Model to assess the river’s water quality is used. The potential application of the fuzzy model has been tested with a case study for the Karoon River. Therefore, a data set collected from 2008 to 2009 from seventeen hydrometric stations along the Karoon River has been used. The most important parameters that affect the water quality namely DO, BOD5, NO3-, Cl-, and EC has been used. Finally, using the Fuzzy Inference Model, the Karoon River’s water quality was classified in three categories: good, moderate and poor. Results of the present study suggest that the fuzzy inference model can be considered as a comprehensive approach for assessing the river water quality in different seasons. Therefore, this methodology offers a suitable and alternative tool to be used in developing effective water management plans.